Relation between pedestrians' safety and traffic noise - Freitas, E. F. (2019)
With the pressure to lower traffic noise limits due to environmental impacts, many questions have been raised regarding pedestrians' safety. Aiming at investigating the effect of traffic noise on crossing behaviour of pedestrians, a virtual environment was reproduced based on data collected from a vehicle passing-by at different speeds and decelerations. In the virtual environment, an experiment with nineteen auditory stimuli was carried out. Eleven participants were asked to signal the moment they thought it was safe to cross the street, without visual information about the car approaching. The Time-to-Collision (TTC) was calculated and compared to the real TTC, to assure that pedestrians' real vs. virtual crossing behaviour was identical. Afterwards, the crossing rate was calculated and correlated with acoustic and psychoacoustic parameters. Loudness was found to be the best indicator for representing the crossing rate, followed by the maximum sound pressure level (SPLmax). Without a visible trend line, Sharpness seemed to have a threshold limit separating high from low crossing rates. These results form the basis to set tyre-road noise limits for safety purposes.